Smoking: Impact on the state budget and its fair taxation - Pavel Hait (Charles University in Prague, Institute of Economic Studies (IES), 2012)
The paper addresses the impact of smoking in the Czech Republic in 2009. The aim is to describe the current facts of tobacco taxation, assess the mortality attributable to smoking, compute the impact of smoking on the Czech state budget, assess consumer price elasticity for cigarettes, and compute a fair excise tax on cigarettes for the Czech Republic as well as the tax which would maximise the benefits of smoking for the state budget. The author defines "fairness" as a situation in which there is no net redistribution of state budget funds between two groups of citizens: non-smokers and smokers. Smokers create benefits (for example, savings on pensions due to their earlier deaths) and costs (for instance, increased healthcare costs) for the state budget. The author searches for a tax rate that would balance smoking-associated costs and benefits. The tax which would maximise net revenues from smoking to the government is also evaluated. These findings were computed for the Czech Republic, 2009: There were 20,693 deaths attributable to smoking. 2.281 billion cigarettes were sold illegally. The costs to the state budget caused by smoking were estimated to 30,310 million CZK, whereas the benefits to 76,225 million CZK. The consumer price own elasticity, controlled for income, was evaluated to be -0.506. Based on these findings and regarding the size of black market, the specific excise tax rate for a cigarette piece to attain the fair taxation should be -0.53 or 4.31 CZK. The specific excise tax rate for a cigarette piece to attain the maximum revenues for state budget is 1.90 CZK.
Keywords: H21; 330; tobacco taxation; economics of smoking; mortality and morbidity caused by smoking; smoking-attributable fractions; Czech Republic